Practical Methods for Expression of Recombinant Protein in the Pichia pastoris System. Issue 6 (23rd June 2021) - Mohammadzadeh, Roghayeh; Karbalaei, Mohsen; Soleimanpour, Saman; Mosavat, Arman; Rezaee, Seyed Abdolrahim; Ghazvini, Kiarash; Farsiani, Hadi
Abstract: One of the most critical challenges of genetic engineering is the expression of recombinant proteins using biological expression systems. Nowadays, different expression systems from bacteria to mammalian tissue culture cells are available for the production of recombinant proteins for medical and industrial purposes. Among various choices, yeast expression systems such as Pichia pastoris are promising candidates. The P. pastoris expression system is a standard tool for the production of biopharmaceuticals and industrial enzymes. It is also considered a unique host for the expression of subunit vaccines which could significantly affect the growing market of medical biotechnology. Using P. pastoris as an expression system for heterologous proteins, this article provides detailed basic protocols for cloning of a recombinant cassette into a suitable expression vector, the transformation of foreign vector DNAs into the yeast by electroporation, and expression and purification of desired recombinant protein. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Cloning of a recombinant cassette into a suitable expression vector Basic Protocol 2 : Transformation of P. pastoris and selection of transformants Basic Protocol 3 : Optimization and large‐scale expression of recombinant proteins Basic Protocol 4 : Purification of recombinant proteins